A framework for safe estradiol modulation in male bipolar disorder: theoretical justification for SERM-enabled adjunctive therapy - Carlson, John (Frontiers in Psychiatry, 2025)
Treatment-resistant bipolar disorder (TR-BD) in males remains a significant clinical challenge, often unresponsive to standard monoaminergic therapies. This paper proposes a novel, sex- informed hypothesis: that adjunctive estradiol, buffered by selective estrogen receptor modulators (SERMs), can therapeutically engage estrogen receptor beta (ER-β) and G protein-coupled estrogen receptor 1 (GPER1) in the male brain, targeting core dysfunctions in TR-BD. Integrating evidence from neuroendocrine, neuroimmune, and synaptic signaling research, we posit that central estrogen receptor activation can restore neuroplasticity, suppress pro- inflammatory cascades, and recalibrate stress responsivity without inducing feminizing systemic effects. Preclinical and translational studies suggest that ER-β and GPER1 activation enhances brain-derived neurotrophic factor (BDNF) expression, modulates CREB and PI3K/Akt pathways, and attenuates interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α) signaling—mechanisms dysregulated in TR-BD. We hypothesize that co-therapy with estradiol and a SERMin male TR-BD will reduce affective instability, cognitive impairment, and stress sensitization via selective activation of ER-β/GPER1, without inducing peripheral feminization. This receptor-targeted strategy offers an endocrine-neutral alternative to existing treatments, with implications for mood disorders, schizophrenia-spectrum illnesses, and trauma-related psychopathology. This framework invites translational trials using biomarker-enriched patient stratification. If validated, it could reshape the role of sex hormones in male psychiatry—not as contraindications, but as precision neuromodulators aligned with neurobiological pathology.